Akulturasi Islam dan Budaya Lokal dalam Tradisi Mangaji Kamatian Pada Masyarakat Lareh Nan Panjang Kabupaten Padang Pariaman - Muhammad Zulfadli; Luqmanul Hakim; Novizal Wendry; Edriagus Saputra (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
The tradition of mangaji kamatian is a form of acculturation of Minangkabau and Islamic culture in Minangkabau. The community interprets this tradition as a form of practice of the sunnah of the Prophet Muhammad. However, some other people interpret this form of tradition as an act of bid'ah (heresy), and some understand it as a form of the practice of jahiliyah, which is haram (forbidden) to carry out. This study uses field research methods using a phenomenological approach with a living hadith model. The results showed that the mangaji kamatian tradition that lives in the Lareh Nan Panjang community is acculturation between Islamic teachings with clear arguments in the Qur’an and hadiths with the customs and cultures that exist in the area. Historically, the mangaji kamatian tradition is a form of interpretation of Shaykh Burhanuddin, a Muslim scholar who spread Islam in Padang Pariaman in the 16-17 century on verses of the Qur’an and hadiths of the Prophet Muhammad SAW related to takziyah. Shaykh Burhanuddin slowly transformed the people who at that time wept when they were stricken by death with a procession of reciting verses from the Koran, prayers, zikir, tahlil and prayers.